# P. 265, Equation (7.16)

From Bill Goodwine's Wiki

Jump to navigationJump to searchThe second line should be

The third line should be:

From Bill Goodwine's Wiki

The second line should be

$=-\lambda \left[-\lambda \left(\lambda ^{2}-\lambda k_{4}+1-k_{3}\right)+k_{2}\right]-\left[-2\left(\lambda ^{2}-\lambda k_{4}+1-k_{3}\right)-k_{1}-1\right]$

The third line should be:

$=\lambda ^{4}-k_{4}\lambda ^{3}+\left(3-k_{3}\right)\lambda ^{2}-\left(2k_{4}+k_{2}\right)\lambda +\left(1-k_{1}-2k_{3}\right)=0.$

- This page was last edited on 16 April 2012, at 14:17.
- Content is available under Attribution-Share Alike 3.0 Unported unless otherwise noted.
- Privacy policy
- About Bill Goodwine's Wiki
- Disclaimers